2015
DOI: 10.1016/j.febslet.2015.01.019
|View full text |Cite
|
Sign up to set email alerts
|

N‐glycosylation and disulfide bonding affects GPRC6A receptor expression, function, and dimerization

Abstract: a b s t r a c tInvestigation of post-translational modifications of receptor proteins is important for our understanding of receptor pharmacology and disease physiology. However, our knowledge about posttranslational modifications of class C G protein-coupled receptors and how these modifications regulate expression and function is very limited. Herein, we show that the nutrient-sensing class C G protein-coupled receptor GPRC6A carries seven N-glycans and that one of these sites modulates surface expression wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 61 publications
3
34
0
Order By: Relevance
“…In addition, we observe a significant boost of the h6A_KGRKLP response by co-transfection with G␣ q (G66D) (Fig. 3B) as we have previously done for m6A (5,9).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, we observe a significant boost of the h6A_KGRKLP response by co-transfection with G␣ q (G66D) (Fig. 3B) as we have previously done for m6A (5,9).…”
Section: Resultssupporting
confidence: 81%
“…Cloning and deorphanization of the mouse (2, 3) and rat (4) GPRC6A orthologs rapidly followed. These studies, together with recent evidence (5) support the existence of GPRC6A as a dimer on the cell surface. However, surprisingly, h6A has been shown to be retained intracellularly and thus does not respond to agonists, which contrasts findings for the mouse, rat, and goldfish orthologs (2,3,6).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…It has been demonstrated that GPRC6A undergoes N-glycosylation (21), which is a posttranslational modification involved in maturation of receptors and correct surface targeting of mature proteins. Oligomerization is another important mechanism that controls surface targeting and/or function.…”
mentioning
confidence: 99%
“…Oligomerization is another important mechanism that controls surface targeting and/or function. For class C receptors in particular, homo-or heterodimerization has proven essential for receptor function, and accordingly homodimerization has been demonstrated for the GPRC6A receptor (2,21). However, the regula-tory mechanisms involved in termination of GPRC6A function remain unknown.…”
mentioning
confidence: 99%